Śāśvata: Ācārya Dayānanda Bhārgava abhinandana grantha - Avasthī, Narendra.; Bhārgava, Dayānanda. (Proffesor Dayanand Bhargava felicitation volume, 1997)
Festschrift in honor of Dayānanda Bhārgava, Sanskritist on his 60th birthday; comprises research papers on Sanskrit and Vadic literature.
Includes bibliographical references.
Festschrift in honor of Dayānanda Bhārgava, Sanskritist on his 60th birthday; comprises research papers on Sanskrit and Vadic literature.
Hindi, English, and Sanskrit.
Keywords: Sanskrit language / Grammar. / http://id.loc.gov/authorities/subjects/sh2008111179; Vedic literature / History and criticism. / http://id.loc.gov/authorities/subjects/sh2008113172; Sanskrit literature / History and criticism. / http://id.loc.gov/authorities/subjects/sh2008111181